10.1016/s1541-9800(07)70161-8 (CrossRef Listing of Deleted DOIs, 2000)
Background Allergic fungal rhinosinusitis (AFRS) is a persistent sinus condition caused by fungal allergies. Endoscopic sinus surgery (ESS) and postoperative systematic and local medical therapies are the most common treatment protocols. Although oral antifungals such as itraconazole are frequently utilised postoperatively, there is increasing interest in alternate therapies that exhibit fewer systemic adverse effects. Manuka honey, recognised for its powerful antibacterial, antifungal and anti-inflammatory characteristics, is a promising alternative. The aim of this study was to assess the efficacy of Manuka honey sinus irrigation in comparison with oral itraconazole for the postoperative management of AFRS. Methods Thirty patients diagnosed with AFRS were recruited for the current randomised clinical trial after ESS. Patients in the two groups randomly received either oral itraconazole (Group A) or Manuka honey sinus irrigation (Group B) for 6 weeks postoperatively. Both cohorts were monitored for 6 months postoperatively. Results Lund-Kennedy endoscopic scores, total IgE levels and SNOT-22 scores were significantly improved in Group B after Manuka honey sinus irrigation. Both groups had similar Lund-Mackay radiological scores and numbers of postoperative sinus infections during the follow-up period. Conclusions Postoperative Manuka honey sinus irrigation is more effective than oral itraconazole for reducing symptoms and preventing the recurrence of AFRS. It is considered a promising therapeutic alternative in the postoperative management of AFRS.